Potent Inhibition of Arterial Thrombosis and Venous Thrombogenesis Subject to Adequate Hemostasis via Disrupting β3/Src Interaction in Platelets - Chen, Jiayi; Liu, Shuang; Shen, Yan; Xiong, Huan; Chen, Chao; Xiao, Bing; Wang, Yun; Jin, Lu; Yu, Wanlin; Xu, Dounan; Ruan, Zheng; Liu, Jingqiu; Yang, Yaxi; Mei, Lianghe; Hua, Li; Luo, Cheng; Zhou, Bing; Wang, Kankan; Xi, Xiaodong; Mao, Jianhua (Thrombosis and Haemostasis, 2025)
Antiplatelet and anticoagulation are the cornerstones for arterial and venous thrombosis, respectively; however, hemorrhage remains a significant clinical challenge. Platelets are crucial for arterial thrombosis and contribute to venous thrombosis. Integrin β3 mediates outside-in signaling, which is critical for thrombosis, while inside-out signaling maintains hemostasis. Targeting the β3/Src interactions to selectively inhibit outside-in signaling offers a promising antithrombotic strategy without compromising hemostasis.To develop more potent small molecules that selectively disrupt the β3/Src interaction, thereby inhibiting arterial and venous thrombogenesis without increasing bleeding risk.Building on the previously identified compound DCDBS84, we developed the structurally modified small molecules C109 and C116, with enhanced affinity for the Src SH3 domain. Their antithrombotic effects on both arterial and venous thrombosis were systematically evaluated through in vitro and in vivo studies. The impact on hemostatic function was assessed using a tail-bleeding model. Additionally, the drug developability of C109 was assessed via pharmacokinetic (PK) and metabolite analysis.C109 and C116 exhibited superior efficacy in disrupting the β3/Src interaction. In vitro and in vivo studies demonstrated that C109 and C116 effectively suppress thrombosis at levels comparable to high doses of the αIIbβ3 antagonist integrilin, without elevating bleeding risk. In the Stenosis Model, C109 and C116 significantly reduced venous thrombogenesis by suppressing platelet activation and neutrophil extracellular trap formation. Additionally, C109 displayed favorable PK properties and robust metabolic stability.These findings identify promising small molecules that inhibit thrombosis while maintaining hemostasis, providing new avenues for safer and more effective clinical management.
Keywords: antiplatelet agent; hemorrhage; thrombosis; venous thrombosis